Implementasi Kurikulum Merdeka pada Pembelajaran Rumpun Pendidikan Agama Islam di MAN 1 Mukomuko Provinsi Bengkulu - Daraqthuni Daraqthuni (UIN Fatmawati Sukarno Bengkulu, 2021)
The purpose of this study is (1) To describe the planning of PAI cluster learning in the independent curriculum at MAN 1 Mukomuko. (2) To describe the implementation of PAI cluster learning in the independent curriculum at MAN 1 Mukomuko. (3) To describe the evaluation of PAI cluster learning in the independent curriculum at MAN 1 Mukomuko. (4) To describe the supporting and inhibiting factors in implementing the independent curriculum at MAN 1 Mukomuko.The type of research is descriptive qualitative, data collection techniques are observation, interviews and documentation. Data analysis techniques are data collection, data reduction, data presentation, conclusions and verification. The subjects of the study were the head of the madrasah, deputy head of the madrasah and teachers. The results of the study (1) The planning of PAI cluster learning in the independent curriculum at MAN 1 Mukomuko has been implemented well, which can be seen from the completeness of the fulfillment of learning devices in accordance with the demands of the independent curriculum, namely: a) Creating learning achievements b) Creating a learning objective flow c) Creating teaching modules d) Carrying out a project to strengthen the profile of Pancasila students (P5), namely 3 themes of local wisdom, Bhinneka Tunggal Ika and Build the soul and body (2) The implementation of PAI cluster learning in the independent curriculum at MAN 1 Mukomuko has gone well, such as carrying out learning activities with a) Preliminary activities (b) Core activities and c) Closing activities. (3) Evaluation of PAI cluster learning in the independent curriculum at MAN 1 Mukomuko has been implemented well according to the assessment in the independent curriculum including: a) Diagnostic assessment. b) Formative assessment. c) Summative assessment. (4) Supporting and inhibiting factors are: 1) Adequate learning facilities and infrastructure. 2) Islamic religious education learning materials are easier and more interesting. 3) Certified teachers. Inhibiting factors are: 1) Electricity often goes out 2) Certain textbooks are incomplete and 3) Limited training and education received by teachers.